On Metric Spaces with Its Major Variants (The Nepali Mathematical Sciences Report, 2024)
A fundamental characteristics of the relative position of points of a space is the distance between them that leads to the idea of a metric space first introduced by M. Frechet in 1906. Metric spaces form a natural environment for exploring fixed points of single and multi-valued mappings. There have been several attempts to extend or to generalize the definition of a metric space in order to obtain possibilities for more fixed points results in Nonlinear analysis.